Race structure in the Mexican collection of common bean landraces - Blair, Matthew W.; Díaz, Lucy M.; Acosta Gallegos, Jorge Alberto (Wiley, 2013)
Mexico is a large bean‐producing country, the second most important in the Western Hemisphere, and the center of origin for common bean (Phaseolus vulgaris L.) as well as many wild relatives or cultigens. Given this long tradition with the crop, Mexican farmers have created a rich resource of native landraces over many millennia, and this germplasm is of value today for modern breeding and gene discovery. The objective of this research was to evaluate the core collection of the national Mexican germplasm repository (Instituto Nacional de Investigaciones Forestales, Agricolas y Pecuarias [INIFAP]) and to determine the diversity and population structure within the germplasm set based on fluorescent microsatellite marker genotyping. The results showed a good separation of races Durango, Jalisco, and Mesoamerica, which were the majority of the landraces, versus a small group of Andean landraces that were all well supported both by population structure analysis and coherent results with principal component analysis and a molecular analysis of variance. Genepool separation has been observed in many previous studies of diversity in common bean but this study was among the first with microsatellites to find separation of the Durango and Jalisco races. The utility of the INIFAP core collection for association mapping studies of traits important to Mexican agriculture is discussed.